The Flint Water Crisis - Wakes, Nakiya (Anglican theological review, 2018)
A personal narrative is presented that discusses the author's experience as a resident of Flint, Michigan who was pregnant and miscarried twice, noting the effects of the city water's lead content on her health and her children's health.